(untitled) (Journal of Comparative & International Higher Education, 2024)
This qualitative study explores the self-conceptualisation of higher education projects (HEPs) relocated out of Russia or created in exile by Russian emigrants after he Russian invasion of Ukraine in 2022. Drawing on semi-structured interviews, analysed by thematic analysis, and discourse analysis of projects’ promo-materials, this paper explores how HEPs formulate their goals and aims concerning the conflict zone–their homeland. The research argues that these projects manage to overcome ‘exiled consciousness’ and appear as a hope-making practice. However, aiming to preserve the relocated academic heritage, HEPs limit their self-reconceptualisation, i.e., further reflection on the continuity of their practice. Along with presenting current narratives, the study suggests further directions for exploration of the imagined future and its materialisation mechanism through educational means in the context of a political and humanitarian crisis, along with the way the international education landscape is being reshaped in it.